Inovasi dalam Pengabdian Masyarakat: Memecahkan Tantangan Pajak Lokal - Dyah Ayu Pramesthi; Elisabeth Marlina; Fatimatuz Zahroh; Sigit Santoso (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Community service is not just charity, but also includes innovative efforts to improve community welfare. This article identifies and analyzes the main challenges in local tax management by local governments, which can hinder community progress and prosperity. Factors such as a lack of efficiency in the tax collection and monitoring process, a lack of public understanding, and an outdated tax system are the main focus of the analysis. Based on the data and information obtained, this article conducts qualitative analysis to understand existing practices and literature. The ever-changing global context demands innovative and sustainable solutions from local governments. Therefore, community service through innovation in local tax management is imperative. Several innovations are proposed, namely digitalization of local taxes, tax education for the community, performance-based tax, citizen participation in tax decision making, partnerships with the private sector. By using these innovations, local governments are expected to be able to create a tax system that is efficient, fair and sustainable. In an era of social and technological change, innovation in community service is a relevant strategy for achieving sustainable development and equal distribution of prosperity. This article summarizes the key role of innovation in addressing local tax challenges, shaping an inclusive local tax future and supporting sustainable economic growth.